2018
DOI: 10.3892/ol.2018.9086
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of arsenic trioxide on tumor cells and the potential underlying mechanisms

Abstract: The human ether-a-go-go related gene (hERG) encodes the rapid delayed rectifier K+ channel. hERG not only serves an important role in heart muscle and cardiomyocyte excitability by regulating action potential repolarization, but also represents a selective advantage for cancer cell proliferation. Arsenic trioxide is a traditional Chinese medicine, which has been previously identified as an efficient tumor suppressor, particularly in the treatment of acute pro-myelocytic leukemia. However, studies have also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The human ether-a-go-go-related gene potassium channel (hERG) has been identified as a novel regulator of growth and death in tumor cells. 13 Zhang et al 14 recently reported dual effects of arsenic trioxide on tumor cells. They reported stimulated proliferation at low doses, associated with increased expression of hERG and accelerated hERG channel activation, and inhibited proliferation at high doses, associated with reduced expression of hERG.…”
Section: Discussionmentioning
confidence: 99%
“…The human ether-a-go-go-related gene potassium channel (hERG) has been identified as a novel regulator of growth and death in tumor cells. 13 Zhang et al 14 recently reported dual effects of arsenic trioxide on tumor cells. They reported stimulated proliferation at low doses, associated with increased expression of hERG and accelerated hERG channel activation, and inhibited proliferation at high doses, associated with reduced expression of hERG.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were visualised using an ECL Western Blotting Detection System (GE Healthcare, Buckinghamshire, England) 26 . To quantify the western blotting data, the intensities of proteins of interest in each gel were firstly normalized to their respective actin intensities, then the normalized intensities were compared with the intensity of the control group and expressed as relative values to their controls 27 .…”
Section: Methodsmentioning
confidence: 99%
“…104 Folding inhibition also has been proposed as a mechanism of the dual tumor suppression and carcinogenicity of arsenic trioxide. 105 Similarly, the antidiarrheal berberine and its derivative, dihydroberberine (Figure 4), have been shown to impair hERG folding in both HEK293 cell lines and guinea pig ventricular cardiomyocytes. 106,107 The inhibition of folding by those drugs results in the reduction of the mature glycosylated form of 155 kDa hERG, which can be easily measured along with immature hERG (135 kDa).…”
Section: Trafficking Inhibitionmentioning
confidence: 97%